Voices and Silences: Exploring Signs of Ideological Subversion in Media Translation in the Arab World - Al-Maryani, Jasim Khalifah Sultan (Al-Adab Journal, 2022)
Translation and interpreting studies in the new millennium started to benefit from the advancements in sociology to account for the translators’ and interpreters’ subjective agency. As human actions and reactions are not always predictable, the agency can play a decisive role in the degree to which translators and interpreters intervene in the tasks they are assigned to accomplish. Different economic, social, political, and ethnic factors may lead them to consciously or sub-consciously involve to prioritize certain interests. The present study assumes that they can actively participate in ideologically subverting the ‘other’ group or community. They can make use of any textual tools at their disposal to feed their institutionalized knowledge and beliefs or ideologies into the texts or utterances they are rendering. They may not hesitate to delete, add, or replace the messages that struggle with them or their group or community’s ideological stands. Actor-network theory is the conceptual framework on which this study is based to disclose and justify possible occasions of subversion. The data are taken from Al-Jazeera and Al-Arabiya live simultaneous interpreting of three political speeches: Iraqi Prime Minister Haider Al-Abadi’s English speech at the 2017 Munich Security Conference and American President Barack Obama’s two speeches entitled ‘A New Beginning’ (delivered June 4, 2009, in Cairo) and ‘A Moment of Opportunity’ (delivered May 19, 2011, in the Department of State). The findings prove that ideological subversion in the interpreting process is inescapable.